ANALYSIS OF THE ELECTROSLAG REMELTING METHOD AND EQUIPMENT FOR ELECTROSLAG CASTING - G. V. Solovej; M. A. Snigir (Литьë и металлургия, 2012)
The analysis of the electroslag refining for electroslag casting is given. its advantages and virtues are given.